Regulatory mechanism of circular RNAs in brain and neurodegenerative diseases - Amelimojarad, Mandana; Amelimojarad, Melika (Frontiers in Molecular Neuroscience, 2025)
Recent advancements in sequencing technology have allowed scientists to study the function and expression of different non-coding RNAs (ncRNAs). Circular RNAs (circRNAs) are increasingly recognized as prognostic and diagnostic biomarkers. These classes of ncRNAs are closed loops that are made from alternative mRNA splicing and can be found in large quantities with their evolutionarily conserved features across different species. These circRNAs can be derived from both coding and non-coding transcript and regulate cellular proteins and the expression of linear mRNA transcripts via their ability to act as miRNA sponges at various levels. Different circRNAs can affect the neurodegenerative disease pathogenesis such as Alzheimer's disease (AD), via altering a variety of methods. However, there is still limited knowledge about circRNAs in brain cells. Therefore, in this review, we will focus on the role of circRNAs in the brain to reveal a new potential therapeutic target and open the door to novel therapies and improved management of brain and neurodegenerative diseases.